Postoperative corneal remodeling after corneal allograft intrastromal ring segment (cairs) implantation for keratoconus: an oct study - Yakut, Burcu; Tanrıverdi, Cafer; Keskin Perk, Fatma Feyza Nur; Aşık Nacaroğlu, Şenay; Altınbaş, Munise; Kılıç, Aylin (My University, 2025)
Objectives: To demonstrate corneal remodeling after corneal allograft intrastromal ring segment (CAIRS) with an anterior-segment optical coherence tomography (AS-OCT). Design: A prospective observational single-center study. Methods: This observational study included keratoconus patients who underwent CAIRS implantation into a stromal tunnel. Topographical, refractive, and visual changes were obtained from the patient records. Epithelial thickness (ET), anterior stromal thickness (AST), allograft corneal ring thickness (ACRT), and posterior stromal thickness (PST) were measured on the first day and 1, 3, 6, and 12 months postoperatively using AS-OCT. Results: The study included 35 eyes of 27 patients with advanced keratoconus. The mean keratometry decreased from 48.26 ± 4.78 D to 44.50 ± 4.42 D at 1-year postoperatively (P = 0.004), mean corrected distance visual acuity increased from 0.29 ± 0.18 to 0.70 ± 0.24 (P < 0.001), and spherical equivalent (SE) decreased from -6.94 ± 4.32 D to -1.44 ± 4.44 D (P < 0.001). The mean AST decreased by 17.39 ± 5.78 μm in the postoperative 1 st month compared to 1 st day after surgery (P = 0.040). No statistically significant variations were observed in AST after the first month. There was no statistically significant difference in the mean ET, ACRT, and PST measurements between follow-up times. Significant negative correlations were found between SE change and ET (r = -0.543, P = 0.023) and between K1 change and ACRT (r = -0.548, P = 0.008). Conclusion: CAIRS is an effective treatment method to improve visual acuity and keratometry measurements and does not cause significant changes in graft thickness or recipient corneal epithelial and stromal thicknesses during the 1-year follow-up period. The observed correlations between SE, keratometry, and corneal thickness suggest that epithelial and stromal remodeling play crucial roles in postoperative outcomes of CAIRS.
Keywords: Anterior-Segment Optical Coherence Tomography; Corneal Allograft Intrastromal Ring Segment Implantation; Corneal Remodeling; Keratoconus